Tantangan Kepemimpinan Sekolah pada Peningkatan Profesionalisme Guru - Hidayah, Vivin; Sholichah, Puput Imroatu; Rofiah, Khusnur; Fathoni, Tamrin (Civiliza Publishing, Indonesia., 2024)
In terms of creating an appropriate learning environment and increasing teacher professionalism, school leadership has an important role. However, on the way to this goal, school principals are often faced with a number of major challenges. From limited resources to conflict management, assuming a school leadership role is never easy. This research method uses a comprehensive literature review approach, this research seeks material from various sources, including research papers, textbooks, and scientific publications. Information was gathered from publications including principal development standards and books on leadership and education. Descriptive data analysis involves identifying major themes, condensing information, and analyzing the results to draw conclusions. The results of this research show that this research looked at a number of challenges that school principals usually face in achieving their goals and potential. Based on this study, several internal and external aspects were identified as the main obstacles in achieving these goals. Challenges in school leadership and increasing teacher professionalism are complex and multifaceted issues. The conclusion is that school leadership has an important role in increasing teacher professionalism, which in turn contributes to improving the quality of education.